Belantamab mafodotin for relapsed or refractory multiple myeloma (DREAMM-2): a two-arm, randomised, open-label, phase 2 study. Issue 2 (February 2020) - Lonial, Sagar; Lee, Hans C; Badros, Ashraf; Trudel, Suzanne; Nooka, Ajay K; Chari, Ajai; Abdallah, Al-Ola; Callander, Natalie; Lendvai, Nikoletta; Sborov, Douglas; Suvannasankha, Attaya; Weisel, Katja; et al.
Summary: Background: Belantamab mafodotin (GSK2857916), an immunoconjugate targeting B-cell maturation antigen, showed single-agent activity in the phase 1 DREAMM-1 study in heavily pre-treated patients with relapsed or refractory multiple myeloma. We further investigated the safety and activity of belantamab mafodotin in the DREAMM-2 study. Methods: DREAMM-2 is an open-label, two-arm, phase 2 study done at 58 multiple myeloma specialty centres in eight countries. Patients (aged ≥18 years) with relapsed or refractory multiple myeloma with disease progression after three or more lines of therapy and who were refractory to immunomodulatory drugs and proteasome inhibitors, and refractory or intolerant (or both) to an anti-CD38 monoclonal antibody with an Eastern Cooperative Oncology Group performance status of 0–2 were recruited, centrally randomly assigned (1:1) with permuted blocks (block size 4), and stratified by previous lines of therapy (≤4 vs >4) and cytogenetic features to receive 2·5 mg/kg or 3·4 mg/kg belantamab mafodotin via intravenous infusion every 3 weeks on day 1 of each cycle until disease progression or unacceptable toxicity. The intention-to-treat population comprised all randomised patients, regardless of treatment administration. The safety population comprised all patients who received at least one dose of belantamab mafodotin. The primary outcome was the proportion of randomly assigned patients in the intention-to-treat population who achieved an overall response, as assessed by an independent review committee. This study is registered with ClinicalTrials.gov, NCT03525678, and is ongoing. Findings: Between June 18, 2018, and Jan 2, 2019, 293 patients were screened and 196 were included in the intention-to-treat population (97 in the 2·5 mg/kg cohort and 99 in the 3·4 mg/kg cohort). As of June 21, 2019 (the primary analysis data cutoff date), 30 (31%; 97·5% CI 20·8–42·6) of 97 patients in the 2·5 mg/kg cohort and 34 (34%; 23·9–46·0) of 99 patients in the 3·4 mg/kg cohort achieved an overall response. The most common grade 3–4 adverse events in the safety population were keratopathy (in 26 [27%] of 95 patients in the 2·5 mg/kg cohort and 21 [21%] of 99 patients in the 3·4 mg/kg cohort), thrombocytopenia (19 [20%] and 33 [33%]), and anaemia (19 [20%] and 25 [25%]); 38 (40%) of 95 patients in the 2·5 mg/kg cohort and 47 (47%) of 99 in the 3·4 mg/kg cohort reported serious adverse events. Two deaths were potentially treatment related (one case of sepsis in the 2·5 mg/kg cohort and one case of haemophagocytic lymphohistiocytosis in the 3·4 mg/kg cohort). Interpretation: Single-agent belantamab mafodotin shows anti-myeloma activity with a manageable safety profile in patients with relapsed or refractory multiple myeloma. Funding: GlaxoSmithKline.